Keyloggers: silent cyber security weapons. Issue 2 (February 2020) - Bhardwaj, Akashdeep; Goundar, Sam
Abstract : Cyber attackers are always seeking to design and push malicious software programs to unsuspecting users, to intentionally steal or cause damage and exploit data on end user systems. Malware types include spyware, keyloggers, rootkits and adware. In the past, script kiddies hacked computers to show off their skills and have fun. Today, hacking computers has become a huge cybercrime industry. Even as systems have improved in terms of both hardware and software, cyber attacks continue unabated. The privilege level at which keyloggers execute is higher than typical malware, which makes them almost impossible to detect and remove. Dr Akashdeep Bhardwaj of the University of Petroleum & Energy Studies, Dehradun, and Dr Sam Goundar of the University of South Pacific, demonstrate how a keylogger can gather keystrokes and screenshots along with online transactions without a scanner being able to detect it. They also suggest a form of virtual keyboard that could defeat this kind of malware.